Sanitary-Microbiological Assessment of Water in Kuyimazar and Tudakul Reservoirs (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article presents the results of a sanitary-microbiological assessment of the water quality in the Kuyimazar and Tudakul reservoirs. A microbiological analysis was carried out to determine the level of contamination and evaluate the suitability of the water for drinking, agricultural, and recreational purposes.